How the prefrontal executive got its stripes. (October 2016) - Barbas, Helen; García-Cabezas, Miguel Ángel
Highlights: The cerebral cortex varies systematically in laminar structure and cellular features. Connections are best summarized within the framework of cortical systematic variation. Prefrontal limbic areas have two-way connections with the amygdala and hypothalamus. Prefrontal cortex has privileged access to the basal ganglia and cerebellar output. The systematic structural variation of the cortex emerges in development. Abstract : Pathways from cortical and subcortical structures give the prefrontal cortex a panoramic view of the sensory environment and the internal milieu of motives and drives. The prefrontal cortex also receives privileged information from the output of the basal ganglia and cerebellum and innervates widely the inhibitory thalamic reticular nucleus that gates thalamo-cortical communication. Connections, in general, are strongly related to the systematic structural variation of the cortex that can be traced to development. Insights from development have profound implications for the special connections of the prefrontal cortex for executive control, learning and memory, and vulnerability in psychiatric and neurologic diseases.